Disparities in Consumer Preferences for Procuring Vegetables Between Traditional and Modern Markets - Zulfida, Ida; Siregar, Nur Mawaddah; Darus, Mozard Bahauddin; Lindawati, Lindawati (Universitas Panji Sakti, 2025)
Consumer preferences for vegetables reflect the decision to buy them in traditional vs contemporary marketplaces, impacted by several circumstances. This article analyzes the impact of pricing, product quality, product completeness, facilities, and services on vegetable purchasing in modern and traditional marketplaces, utilizing the Structural Equation Modeling (SEM) approach within the Smart-PLS 4.0 program. The research utilized primary data collected from 96 participants across six modern and traditional marketplaces in Medan City. The findings of this study reveal disparities in the factors influencing traditional and modern marketplaces. In conventional marketplaces, price, product variety, and service substantially influence customer preferences for vegetables, although product quality and amenities do not significantly impact these choices. In contemporary marketplaces, product quality, facilities, and services substantially influence customer preferences for purchasing vegetables, although price and product completeness have no major impact on these choices. Affordability, product comprehensiveness, and service quality are essential considerations for consumers shopping in traditional marketplaces. This component must be sustained to be competitive in contemporary markets. Moreover, amenities are a crucial issue to consider for the coexistence of traditional markets alongside modern marketplaces.